A Review on Emoji Entry Prediction for Future Finance Market Analysis Using Convolutional Neural Network - PC Lakshmi Narayanan; Kishore Kunal; Veeramani Ganesan; Sudhakar Ganesan; Anitha Jaganathan; Madeshwaren, Vairavel (International Journal of Computational and Experimental Science and Engineering, 2025)
Textual and financial data in social media has come a long way in the present. Emojis, the primary focus of this study piece, allow emotions to be visually represented thanks to the advent of text-based digital communication. By adding visual currency attractiveness to text, emojis in digital communication enhance communication and open up new channels for innovation and exchange. The neural network model for text-based emoji entry prediction is highly optimised, however because of little knowledge in this field, it is more difficult to predict future emojis from images all the finance symbols. Emojis are a great alternative to linguistically independent, sentiment-aligned embeddings since they are consistent and convey a clear sentiment signal NSE and BSE market. Compared to models for text, models for symbolic description have received less attention. In this study,Main researchers employed CNN architecture for image classification together with an emoji2vec embedding into the word2vec model to predict emoji from photos apply in finance sector and finding. Additionally, we performed a sentiment analysis on the text to forecast upcoming emoji labels added. Our approach effectively communicates how the emojis relate to one another. The length of the search for incoming image-based emoji predictions has been optimised using this model.